Interactive Visualization of the Printed Circuits Tracing Algorithms for Educational Purposes - D. O. Petrov (Цифровая трансформация)
A software module that allows interactive demonstration of maze routing algorithms for tracing printed conductors, which, during their operation, use a grid representation of a discrete working space of a printed circuit board has been developed. The main difference between the developed module and the software of similar purpose is the possibility of step-by-step annotated execution of various algorithms for tracing printed conductors with the possibility of changing the order of routing user-specified conductors. The interrelation of algorithms for finding the shortest paths on graphs and algorithms for tracing printed conductors and the influence of the order of making connections between pairs of contact pads on the length of printed electrical connections are considered. An analysis of the advantages and disadvantages of the wave algorithm (Lee algorithm) and the heuristic algorithm A* was carried out with a description of their step-by-step operation. The use of the development is justified when giving lectures and conducting laboratory research on the theoretical foundations of automation systems for the design of radio electronic equipment and contributes to solving the complex problem of digitalization of the educational process with the help of visualization programs that allow you to observe the results of the algorithms they implement on various sets of initial data.